UJI VARIABEL INDEKS KONDISI GELOINA COAXANS YANG BERASAL DARI KAWASAN KONSERVASI MANGROVE DAN BEKANTAN (KKMB) KOTA TARAKAN - ,, Ahmadi; ,, Rosmianto; ,, Ferdinandus; Salim, Gazali (Jurnal Harpodon Borneo, 2013)
Tarakan has a diversity of marine life that live in the west coast city of Tarakan, from the phylum Molusca species of kerang Kapah is Geloina coaxans. The purpose of this study was to determine the quality of the meat from the kerang kapah (Geloina coaxans) by measuring the condition index (body shape and know the environmental habitat of kerang Kapah (Geloina coaxans) in terms of water quality (physical and chemical parameters).Methods of research used descriptive method. Sampling using purposive sampling method on two different stations. Station 1 in the area of 9 ha KKMB and Station 2 in the expansion area of 13 Ha KKMB. Sampling using a plot 15m x 15m x 10 cm. Sampling was done at the time of sea water in low tide conditions.The results in the condition index obtained station 1 is the highest percentage in the form of the body is at 72.9 % and the smallest percentage in the form of lean body shape at 1.4 % and the percentage of body fat obtained form by 25.7 %. The results of the analysis of the condition index at station 2 obtained the highest percentage of body shape are at 60.4 % and the smallest percentage of lean body shape by 1% and the percentage of body fat obtained form by 38 % . In addition there is a 1 piece Geloina itupula coaxans that there is no meat (error). Habitats Geloina coaxans in the area KKMB 9 Ha is salinity the value range of 26,9555+0,205 ppt ; DO of 4,97+0,89 ppm ; pH of 7,51+0,27 ; temperatures of 28,35+0,21 0 C ; TDS at 17,46+3,76ppm. Habitats Geloina coaxans in the area KKMB 13 Ha is salinity has a value range of 27,07+0,17ppt ; DO of 4,38+0,25 ppm, pH of 7,39+0,1 ; temperatures of 28,68+0,17 0C ; TDS amounting to 21,155+0,215ppm.keywordsCondition index , Kerang Kapah , Geloina coaxans , KKMB , Tarakan